The colors of violence cultural identities, religion, and conflict - Kakar, Sudhir 1938-2024 (Univ. of Chicago Press, 1996)
Through riveting case studies, Kakar explores cultural stereotypes, religious antagonisms, ethnocentric histories, and episodic violence to trace the development of both Hindu and Muslim identities. He argues that in early childhood the social identity of every Indian is grounded in traditional religious identifications and communalism. Together these bring about deep-set psychological anxieties and animosities toward the other